A religious people in a laic State: contributions of Protestant Reform to tolerance in secular space - Krüger, Sabrina Alves de Jesus da Silva; Westphal, Euler Renato (Vox Scripturae - Revista Teológica Internacional, 2018)
This research shows the relationship between the State and the Church. The laic state is conceptualized as a state based on Christian tradition, and is shaped by Scripture, through its legal laws and regulations of society. This State perspective based on the Protestant tradition is visible from Luther, who affirmed the need to establish two distinct kingdoms: the State and the Church. Habermas, from Kant, helps to develop the understanding of a democratic State. Both Kant and Habermas are grounded in Luther’s understanding, which distinguishes the community of faith (Church) from the ethical community (State). The democratic State must guarantee the coexistence between citizens with different beliefs, through mutual tolerance. In Brazil, the laic State is sometimes confused with a declared atheistic State.